Effects of Physiological Condition on Aspects of Repeat Spawning in Female Steelhead Reconditioned in Captivity. Issue 2 (18th February 2020) - Jenkins, Laura E.; Pierce, Andrew L.; Caudill, Christopher C.; Graham, Neil D.; Medeiros, Lea R.; Hatch, Douglas R.; Nagler, James J.
Abstract: Physiological condition (hereafter shortened to "condition") influences survival, spawning schedules, and reproductive effort in salmonids. In iteroparous females, the effects of first spawning on condition could result in trade‐offs with future reproduction, mediated by postspawning survival, repeat spawning schedule (i.e., consecutive or skip spawning), or reproductive effort. However, which aspects of condition affect these outcomes and when they are sensitive to condition are not well understood. These issues were examined in highly energy‐depleted hatchery‐origin female summer steelhead Oncorhynchus mykiss that were undergoing postspawning reconditioning in captivity. Measures of condition and reproductive characteristics (i.e., fecundity, egg size, and total egg mass [TEM]) at first spawning were examined for their effects on postspawning survival and future spawning schedules, and condition was tracked during reconditioning to examine effects on reproductive characteristics at repeat spawning. The levels of plasma osmolality and triglycerides measured at first spawning were positively correlated with survival probability, suggesting that survival depends on the ability to maintain homeostasis and access stored energy. Surprisingly, size‐standardized TEM measured at first spawning was positively correlated with the probability of consecutive spawning, providing no support for the hypothesized trade‐off between current and future reproduction. This finding instead suggests that both first‐spawning reproductive effort and consecutive spawning may be influenced by condition at earlier points. Plasma triglycerides and growth rates at sampling points 10–20 weeks after first spawning were strongly correlated with size‐standardized egg size and TEM at consecutive spawning, suggesting that reproductive effort and its allocation to egg size and fecundity depend on energetic status during early oogenesis. These results indicate that condition influences survival, repeat spawning schedules, and reproductive characteristics in female steelhead up to a year or more before repeat spawning. If more broadly applicable, these relationships could provide insight into the mechanisms that link environmental conditions with reproductive characteristics in salmonids and other species.